Gas sensors : materials and devices - Ma, Jianmin (Ph. D. in materials physics and chemistry) (IOP (Series). Release 21., 2021)
This book reviews the developments and applications of traditional and emerging materials for gas sensors. Each chapter considers a sensor material and discusses the mode of operation, intrinsic material properties, preparation, device construction and areas of application opened by the novel modes of action and properties of the sensing material. With coverage spanning n- and p-type metal oxides, graphene, 2D metal chalcogenides, carbon nanotubes, ionic liquids and conducting polymer composites this up-to-date synthesis will provide invaluable reading for industrial and academic researchers and engineers developing and exploiting new materials for the increasingly diverse areas of applications for modern gas sensors.